Comparative characteristics of human thalamus parameters in the first period of mature age and in senile age in mesocephals - A. A. Balandin; L. M. Zheleznov; I. A. Balandina (Сибирский научный медицинский журнал, 2021)
The problem of demographic aging intensity growth is increasingly raised in the scientific community. Patients belonging to the senile age group have a number of reasons that reduce their quality of life, as well as reduce the effectiveness of treatment and rehabilitation. The most important information node involved in providing functions such as an integrative role in cognition, starting from learning and memory and ending with flexible adaptation is the structure of the intermediate brain – the thalamus. The aim of the study was to conduct a comparative analysis of agerelated morphometric characteristics of human thalamuses in the first period of adulthood and in old age according to magnetic resonance imaging. Material and methods. The results of morphometric study of the thalamuses of 83 people were analyzed, which were divided into two groups based on their age. Group I included 46 people of the first period of Mature age, group II included 37 people of senile age. All patients had a history of diseases and injuries of the Central/peripheral nervous system, alcohol and drug addiction, and were right-handed. The transverse, longitudinal, and vertical parameters of the thalamuses in both hemispheres of the brain were determined. Results. It was found that the parameters of the thalamus prevail in the first period of adulthood in both men and women (p<0.01). At the same time, there was no statistically significant difference between the morphometric parameters of the thalamuses in the hemispheres, but there was a tendency to a predominance of linear dimensions in the left thalamus (p>0.05). We found a tendency to slightly exceed the indicators of the thalamus in men in comparison with the indicators established in women (p>0.05). Conclusion. The results obtained can serve as starting points as the equivalent of the anatomical age norm of the human thalamus in the first period of adulthood and senile age, which in the future will allow for a personalized approach in medical practice.